The Relationship of usingBirth Ball with The Intensity of Pain - Jasmi Jasmi; Ani Laila; Emi Irmawati (Journal of Maternal and Child Health Sciences (JMCHS), 2021)
AbstractBackground: The process of childbirth is identical to pain that can cause birthing mothers to feel anxious. When the mother in labor feels anxious, the body will spontaneously release catecholamine hormones, namely epinephrine and norepinephrine. This hormone can cause complications for both mother and fetus. One of the non-pharmacological methods that can be used to treat labor pain is the use of a birth ball. Purpose: of this study was to determine the relationship between the use of birth balls and the intensity of maternal pain at the Pratama Bhakti Clinic, Pekanbaru City. This type of research is an experimental study with a pretest-posttest control group design. The population of this study were all mothers who gave birth normally at the Pratama Bhakti Clinic, Pekanbaru City for the period March-April 2017, totaling 31 people. The sample of this study amounted to 20 people who were taken by purposive sampling technique. Processing and analysis of data is carried out in a computerized manner. Results: of statistical tests using Mann-Whitney showed that there was a significant difference in pain intensity between the groups of mothers who gave birth using a birth ball and who did not use a birth ball (p = 0.000). Conclusion: In an effort to reduce labor pain, it is recommended that the Pratama Bhakti Clinic apply the use of birth balls as an alternative to reduce labor pain.